2023
DOI: 10.1002/hsr2.1116
|View full text |Cite
|
Sign up to set email alerts
|

Serial SOFA‐score trends in ICU‐admitted COVID‐19 patients as predictor of 28‐day mortality: A prospective cohort study

Abstract: Background and Aim The efficacy of Sequential Organ Failure Assessment (SOFA) score as predictor of clinical outcomes among ICU‐admitted COVID‐19 patients is still controversial. We aimed to assess whether SOFA‐score in different time intervals could predict 28‐day mortality compared with other well‐acknowledged risk factors of COVID‐19 mortality. Methods This observational prospective cohort was conducted on 1057 patients from March 2020 to March 2022 at Masih Daneshva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…The study by Ferreira and collaborators found that a SOFA score of 9 or above is a good predictor of mortality risk. [9][10][11] Therefore, a SOFA score 9 was selected as the cut off for triaging of patients increased risk of death.…”
Section: Nv-icu Patientsmentioning
confidence: 99%
“…The study by Ferreira and collaborators found that a SOFA score of 9 or above is a good predictor of mortality risk. [9][10][11] Therefore, a SOFA score 9 was selected as the cut off for triaging of patients increased risk of death.…”
Section: Nv-icu Patientsmentioning
confidence: 99%